2016
DOI: 10.1038/cr.2016.119
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory phosphorylation of Cdk1 mediates prolonged prophase I arrest in female germ cells and is essential for female reproductive lifespan

Abstract: A unique feature of female germ cell development in mammals is their remarkably long arrest at the prophase of meiosis I, which lasts up to 50 years in humans. Both dormant and growing oocytes are arrested at prophase I and completely lack the ability to resume meiosis. Here, we show that the prolonged meiotic arrest of female germ cells is largely achieved via the inhibitory phosphorylation of Cdk1 (cyclin-dependent kinase 1). In two mouse models where we have introduced mutant Cdk1T14AY15F which cannot be in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 48 publications
1
35
0
Order By: Relevance
“…; Adhikari et al . ). Further, changes in the specific phosphorylation status of MPF and its cross talk with mitogen‐activated protein kinase (MAPK) have been reported during meiotic exit from metaphase‐II (M‐II) arrest in rat and mouse oocytes (Huo et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Adhikari et al . ). Further, changes in the specific phosphorylation status of MPF and its cross talk with mitogen‐activated protein kinase (MAPK) have been reported during meiotic exit from metaphase‐II (M‐II) arrest in rat and mouse oocytes (Huo et al .…”
Section: Discussionmentioning
confidence: 97%
“…CDK1-cyclin-dependent kinase, also known as CDC2, is a catalytic subunit of a protein kinase complex, also identified as the M-phase promoting factor, responsible for permitting mitosis to begin, and is similar among all eukaryotes. Adhikari et al (2016) proved that sustaining the prolonged meiotic arrest in female germ cells relies on the constant suppression of CDK1 activity, which is largely achieved by inhibitory phosphorylation of CDK1. This process is essential for safeguarding the integrity of the DNA in the growing oocytes, which has a positive effect on preserving the germ cell pool.…”
Section: Markers Of Granulosa Cells During In Vitro Culturementioning
confidence: 99%
“…This process is essential for safeguarding the integrity of the DNA in the growing oocytes, which has a positive effect on preserving the germ cell pool. Disturbances in this processes cause the interruption of prophase I arrest, leading to a premature loss of female germ cells (Adhikari et al, 2016). Reis et al (2006) showed that, in fully grown mouse oocytes, the activity of CDK1 remains suppressed.…”
Section: Markers Of Granulosa Cells During In Vitro Culturementioning
confidence: 99%
“…Four independently targeted ES cell clones were injected into C57BL/6 blastocysts to produce the chimeras. Mice with the Spdya loxP allele of C57BL/6J background were crossed with Zp3-Cre transgenic mice of C57BL/6J background (23,24) to delete exon 2 and generate Spdya +/− mice. Mice were housed under controlled environmental conditions with free access to water and food.…”
Section: Methodsmentioning
confidence: 99%